Para kay ama - Tan, Relyn Angkuan 1990-; Alfonso, Grave Javier (2012)
"The film is about a young Tsinoy* who discovers that she has a half-brother and meets him for the first time on the last day of her father's wake. Para Kay Ama tells the story of Hannah, a 28-yeaer old Tsinoy, as she deals with the recent passing of her businessman father William Huang in a car accident. During Huang's wake, a surprising revelation unfolds as Hannah discovers and meets her half-brother for the first time. As Hannah faces the challenge of dealing with acceptance and forgiveness on the last day of the wake, she experiences a rollercoaster of emotions before finally laying her father to rest. Hannah, the film protagonist centers on the feminist film theory, which asserts equal opportunities for women as the premise of the story, is set in a Chinese-Filipino family. The issue on gender roles plays an important part in the framework of Hannah's story since patriarchy is the norm in her cultural background. Defending equal political, economic, and social rights and equal opportunities for women is the main point of feminism. In this case, equal opportunities socially and culturally will be shown more in the film. The treatment of the cinematography caters to the influence of social realism following closely the character's movement and emotions throughout the entire film in real time."
Vita.
Undergraduate thesis (A.B. Film and Audio Visual Communication)--University of the Philippines, Diliman.
Keywords: Para Kay Ama (Short film).; Short films -- Philippines